Promises and Pitfalls of Health Information Technology for Home- and Community-Based Services. (May 2021) - Ahluwalia, Sangeeta C.; Friedman, Esther; Siconolfi, Daniel; Saliba, Debra; Phillips, Jessica; Shih, Regina
Background: Health information technology (HIT) use in home- and community-based services (HCBS) has been hindered by inadequate resources and incentives to support modernization. We sought to understand the ways the Medicaid Balancing Incentive Program (BIP) facilitated increased use of HIT to increase access to HCBS.Method: Qualitative analysis of interviews with 30 Medicaid administrators, service agency providers, and consumer advocates.Results: Although stakeholders perceived several benefits to greater HIT use, they highlighted critical challenges to effective adoption within the long-term services and supports (LTSS) system, including lack of extant expertise/knowledge about HIT, the limited reach of HIT among rural and disabled beneficiaries, burdensome procurement processes, and the ongoing resources required to maintain up-to-date HIT solutions.Conclusion: The structural reforms required by BIP gave states an opportunity to modernize their HCBS systems through use of HIT. However, barriers to HIT adoption persist, underscoring the need for continued support as part of future rebalancing efforts.